Cambio del modelo de gestión de riesgo durante el proceso eruptivo del volcán Tungurahua caso cantón Penipe período 1999-2017. - Guilcapi Baldeón, Alex Javier (2019)
The identification of the stages in the risk management in a complementary way to the field study allowed to evaluate the model for disasters during the eruptive process of the Tungurahua volcano, in the Penipe canton during the 1999-2017 period. The analysis of the management system proposed by Baas, Ramasamy, Dey de Pryck & Batista is the theoretical model used to approach the analysis of the change in the management model. The application of an in-depth interview, an exhaustive review of the regulations, antecedents and response to the eruptive disaster of the Tungurahua volcano allowed an evaluation of what happened during that historical period of time to later give way to the respective conclusions related to the institutional aspects, educational, normative to identify the changes in the handling of disasters of the canton Penipe until the present time.